Production of carotenoids and lipids by Dunaliella tertiolecta using CO2 from beer fermentation. Issue 6 (June 2015) - Chagas, A.L.; Rios, A.O.; Jarenkow, A.; Marcílio, N.R.; Ayub, M.A.Z.; Rech, R.
Graphical abstract: Highlights: An integrated system of photobioreactor and yeast fermentation was studied. The CO2 profile affected the photobioreactor pH and the microalgae specific growth rate. The CO2 -enriched cultures showed higher lipid and carotenoid content in the biomass. The integrated system was validated using CO2 from beer production. Abstract: In this study, we evaluated the effect of growing Dunaliella tertiolecta microalgae using CO2 from brewing on the production of lipid and carotenoid-rich biomass. An integrated system of microalgae photobioreactors and yeast fermenters was used, thus providing biological CO2 continuously to the microalgae culture. Yeast cultures were first carried out in fermenters using synthetic medium. With a step-wise increasing glucose concentration from 10 to 60 g L −1, the CO2 that came from 24 h yeast cultivation gave the highest biomass formation, carotenoids and lipid contents, and productivities by the microalgae. Reproduction of these experiments using beer fermentation instead of synthetic medium was carried out using different volumes of wort coupled to microalgae cultivations. The values obtained for microalgae cultures when using CO2 from beer fermentation were 1.10 ± 0.05 g L −1 of biomass, 0.18 ± 0.01 g L −1  day −1 of biomass productivity, 0.58 ± 0.06 day −1 specific growth rate, 4.74 ± 0.59 mg g −1 of carotenoids per biomass dry weight, 0.86 ± 0.06 mg L −1  day −1 of carotenoids productivity, and 135 ± 4 mg g −1 of lipids. These values are almost twice as high as the values observed for control cultivations in which atmospheric CO2 was used, showing that the integration system of yeast fermenters and microalgae photobioreactors is an interesting alternative to improve biomass formation and product contents. All D. tertiolecta cultures showed the same carotenoids profile, being lutein the major carotenoid (46.7 ± 2.0% of total carotenoids).